TINGKAT KEMANDIRIAN BELAJAR SISWA DITINJAU DARI IMPLEMENTASI LITERASI DIGITAL SISWA SMA NEGERI 2 SUKOHARJO - Dhimas Arsyad Arrajiv; Miftahul Arifah B. B; Tyas Wahyuningsih; Kartini Kartini; Laili Etika Rahmawati (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
Since the Covid-19 virus attacked Indonesia, which has an impact on the education sector. Which transforms face-to-face learning systems into distance learning / online. This online learning encourages digital literacy at its peak, because all learning is online based and uses communication tools. Digital literacy is a solution in this pandemic with all the conveniences and can be accessed at any time, this digital literacy gives rise to the independent learning method. Independent learning is learning on one's own initiative and without someone's supervision, so that students are required to understand the learning material themselves without being supervised by the teacher. This study aims to determine the level of learning independence in terms of digital literacy implementation. The method used in this research is qualitative. The results of this study prove that the level of learning independence in terms of digital literacy implementation is very low, due to several factors. Teachers should provide motivation, give praise and support to their students in order to increase learning independence.